Nitrogen removal and nitrogen functional gene abundances in three subsurface wastewater infiltration systems under different modes of aeration and influent C/N ratios. (October 2017) - Pan, Jing; Qi, Shiyue; Sun, Yafei; Jiang, Yingying; Zhao, Ning; Huang, Linli; Sun, Yining
Highlights: C/N ratio and aeration mode significantly affected nitrogen removal. High C/N ratio of 12 and TN removal rate were achieved in the aerated SWIS. Aeration raised amoA, nxrA, narG, napA, nirK, nirS, qnorB and nosZ abundances. Abstract: Matrix DO, nitrogen removal and nitrogen functional gene abundances in non-aerated (NA), continuously aerated (CA) and intermittently aerated (IA) subsurface wastewater infiltration systems (SWISs) under different influent C/N ratios were studied. Aeration created aerobic condition in 50 cm depth and did not change anoxic or anaerobic condition in 80 and 110 cm depths, which enhanced NH4 + -N and TN removal and the enrichment of nitrogen removal functional genes (amoA, nxrA, narG, napA, nirK, nirS, qnorB and nosZ) compared to NA SWIS, especially under high influent C/N ratio. High TN removal rate (89.6%) was obtained in IA SWIS under the influent C/N ratio of 12, which was higher than that in CA SWIS (87.1%). The results suggested that intermittent aeration was a reliable option to achieve high TN removal in SWISs, especially under high influent C/N ratio.